Interactions between DNA-bound repressors govern regulation by the λ phage repressor - Johnson, Alexander D. (1979)
The λ phage repressor binds cooperatively to the three sites in the right operator (O(R)) according to the following pattern. If the DNA is wild type, O(R)1 and O(R)2 are filled coordinately because of interactions between repressor dimers bound to these two sites. Site O(R)3 is filled only at higher repressor concentrations. In contrast, if O(R)1 is mutant, O(R)2 and O(R)3 are filled coordinately because of interactions between repressors bound to these sites. In this case, the affinity of O(R)3 is increased and that of O(R)2 is decreased relative to the wild type. We infer that a repressor dimer bound to the middle site O(R)2 can interact either with another repressor dimer bound to O(R)1 (wild-type case) or, alternatively, with one bound to O(R)3 (mutant O(R)1 case). We argue that these repressor interactions are mediated by protein-protein contacts between adjacent repressor dimers, because the isolated amino-terminal domains of repressor bind to the operator sites noncooperatively. The cro protein of phage λ, a second regulatory protein, which recognizes the same three sites in O(R) as does repressor, binds non-cooperatively. Experiments performed in vivo show that regulation of gene expression by repressor can be influenced critically by cooperative interactions. We demonstrate that the effect of repressor in a lysogen on the activity of the promoter P(RM) can be changed from activation to repression by deletion of O(R)1. We explain this effect in terms of the alternative cooperative interactions described above.